Compensation in the Post‐FIN 48 Period: The Case of Contracting on Tax Performance and Uncertainty1. (21st July 2015) - Brown, Jennifer L.; Drake, Katharine D.; Martin, Melissa A.
Abstract: Academic and anecdotal evidence indicates that incentive systems often provide short‐term payouts without regard for long‐term consequences. New detailed disclosures mandated by FIN No. 48, Accounting for Uncertainty in Income Taxes, enable us to use a tax setting to investigate whether boards adjust performance‐based pay for uncertainty. We find managers' bonus payouts are positively associated with tax performance; however, bonus payouts are lower when measures of ex ante tax uncertainty are higher. Our results are robust to tests of alternative explanations including financial reporting aggressiveness, overall firm risk, and other forms of compensation. Further, we document that the relation between bonus compensation and tax performance has changed in the post‐FIN No. 48 period. Specifically, we identify a significant association between bonus payout and GAAP ETR only in the pre‐FIN No. 48 period and a significant association between bonus payout and cash ETR only in the post‐FIN No. 48 period, suggesting that the relation between compensation and tax avoidance should be examined carefully with particular attention to the post‐FIN No. 48 period.